Protection and Real Incomes Once Again - Ethier, Wilfred J. (Quarterly Journal of Economics, 1984)
Journal Article Protection and Real Incomes Once Again Get access Wilfred J. Ethier Wilfred J. Ethier University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 99, Issue 1, February 1984, Pages 193–200, https://doi.org/10.2307/1885727 Published: 01 February 1984